1995
DOI: 10.1007/bf00311697
|View full text |Cite
|
Sign up to set email alerts
|

The use of cyanoacrylate tissue adhesive in high-risk intestinal anastomoses

Abstract: The success of every intestinal surgical procedure primarily depends on correct technical execution of the intestinal sutures. Despite the continuing improvements in intestinal synthesis techniques and the introduction of mechanical staplers, the risk of anastomotic dehiscence remains a major concern. For high-risk anastomoses, defined as those performed under critical conditions, n-butyl-2-cyanoacrylate tissue adhesive allows for quick sealing of the two stumps and supports the physiological wound-healing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 19 publications
2
30
0
8
Order By: Relevance
“…Em relação à concentração de granulomas, também não se observou diferença entre os grupos. Outros pesquisadores 32 também estudaram a aplicação dos adesivos sintético e biológico nas anastomoses intestinais e constataram formação de granuloma tipo corpo estranho 33 . O estudo comparativo entre a cola sintética e biológica demonstrou que tanto uma como a outra pode ser utilizada na síntese cirúrgica como suplemento e reforço de sutura.…”
Section: Discussionunclassified
“…Em relação à concentração de granulomas, também não se observou diferença entre os grupos. Outros pesquisadores 32 também estudaram a aplicação dos adesivos sintético e biológico nas anastomoses intestinais e constataram formação de granuloma tipo corpo estranho 33 . O estudo comparativo entre a cola sintética e biológica demonstrou que tanto uma como a outra pode ser utilizada na síntese cirúrgica como suplemento e reforço de sutura.…”
Section: Discussionunclassified
“…Because histopathologic studies of cyanoacrylate-applied tissues revealed severe tissue reaction and inflammation, long-chain derivatives such as butyl cyanoacrylate and octyl cyanoacrylate were developed. These latter moieties lacked histotoxicity and were found to be safe for in vivo applications [12,15,[20][21][22]. In our study, histotoxicity was not evaluated; but it is known from the previous studies that mild to moderate tissue reaction with mononuclear cell migration and giant cell formation that was similar to those observed by the use of polyglactin 910 sutures might have been present [14,19].…”
Section: Discussionmentioning
confidence: 78%
“…El N-butil-cianocrilato o N-butil-2-cianocrilato, siendo también de cadena larga, ha demostrado particularmente poseer una respuesta inflamatoria mínima, conservando sus propiedades adhesivas 5,10,15 por lo que, de acuerdo a estudios, impresiona que se ha ido aumentando su utilización principalmente a nivel europeo, por ejemplo en cirugía abdominal, en anastomosis intestinales de alto riesgo 16 , o nefroptosis 17 , con comunicación de buenos resultados.…”
Section: Discussionunclassified